Between dissent and power : the transformation of Islamic politics in the Middle East and Asia - Teik, Khoo Boo; Hadiz, Vedi R.; Nakanishi, Yoshihiro; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
This study examines the collective progression of Islamic politics between points of dissent and positions of power. It brings about a more a serious understanding of Islamic politics by critically tracing the pathways by which Islamic politics has been transformed in the Middle East and Asia.
Keywords: Islam and politics; Dissenters -- Middle East; Dissenters -- Asia; Middle East -- Politics and government -- 1979-; Asia -- Politics and government -- 21st century